Evaluation of the Flinders Technology Associates Cards for Storage and Temperature Challenges in Field Conditions for Foot‐and‐Mouth Disease Virus Surveillance. Issue 6 (17th January 2015) - Madhanmohan, M.; Yuvaraj, S.; Manikumar, K.; Kumar, R.; Nagendrakumar, S. B.; Rana, S. K.; Srinivasan, V. A.
Summary: Foot‐and‐mouth disease virus (FMDV) samples transported to the laboratory from far and inaccessible areas for diagnosis and identification of FMDV pose a major problem in a tropical country like India, where wide fluctuation of temperature over a large geographical area is common. Inadequate storage methods lead to spoilage of FMDV samples collected from clinically positive animals in the field. Such samples are declared as non‐typeable by the typing laboratories with the consequent loss of valuable epidemiological data. In this study, an attempt was made to evaluate the robustness of Flinders Technology Associates (FTA) cards for storage and transportation of FMDV samples in different climatic conditions which will be useful for FMDV surveillance. Simulation transport studies were conducted using FTA impregnated FMDV samples during post‐monsoon (September–October 2010) and summer season (May–June 2012). FMDV genome or serotype could be identified from the FTA cards after the simulation transport studies with varying temperature (22–45°C) and relative humidity (20–100%). The stability of the viral RNA, the absence of infectivity and ease of processing the sample for molecular methods make the FTA cards an useful option for transport of FMDV genome for identification and type determination. The method can be used routinely for FMDV research as it is economical and the cards can be transported easily in envelopes by regular courier/postal systems. The absence of live virus in FTA card can be viewed as an advantage as it restricts the risk of transmission of live virus.